The effectiveness and safety of physical activity and exercise on women with endometriosis: A systematic review and meta-analysis - Min Xie; Xuemei Qing; Hailong Huang; Linyun Zhang; Qin Tu; Hongying Guo; Jing Zhang (PLoS ONE, 2025)
Background Endometriosis is a debilitating, chronic disease that affects approximately 10% of women of reproductive age worldwide. The most common symptom is chronic pelvic pain, which leads to a reduced quality of life and requires lifelong treatment. The current standard of care for endometriosis is pain management, which consists mainly of medical and surgical treatment. Appropriate physical activity (PA) and exercise can help manage both physical and psychological symptoms of chronic conditions. Consequently, this systematic review and meta-analysis was designed to assess the effectiveness and safety of PA and exercise in women with endometriosis. Methods We searched the published literature in Pubmed, Medline, Embase, The Cochrane Library, and Web of Science. Randomized controlled trials (RCTs) were obtained to assess the effects of physical activity and exercise on women with endometriosis. The random or fixed effects model was used to analyze the data in meta-analysis. The results were expressed as weighted mean differences (WMD) and their corresponding 95% confidence intervals (CIs). Results Six RCTs were identified in our systematic review, involving 251 patients. The results indicated that physical activity and exercise have a beneficial impact on quality of life, pain intensity, mental health, pelvic floor dysfunction, and bone density. However, due to the heterogeneity of the outcome measures and the incomplete reporting of the results in the studies included in this review, only a simple meta-analysis of two studies could be performed. The meta-analysis demonstrated that physical activity and exercise have a significant impact on the improvement of quality of life, particularly in the context of pain (P <0.0001), control and powerlessness (P <0.00001), and emotional well-being (P = 0.006). Conclusion The present review indicates that physical activity and exercise have beneficial effects on the treatment of symptoms associated with endometriosis, particularly in terms of improving quality of life and providing pain relief. Due to the limitation in the quality of involved studies and the short duration of treatment, more RCTs with high-quality, long-term duration are needed for further validation. Trial registration Systematic review registration: Registration number: CRD 42024547551.